Woody species diversity and coffee production in remnant semi-natural dry Afromontane Forest in Zegie Peninsula, Ethiopia - Belay, B.; Zewdie, S.; Mekuria, Wolde; Abiyu, A.; Amare, D.; Woldemariam, T. (Springer, 2019)
The forest structure and composition of Afromontane forests in Ethiopia, where Arabica coffee is originated and grown as an understorey shrub, have been deteriorating following intensive and ever-increasing management interventions for coffee production. The study conducted in Zege Peninsula Dry Afromontane forest to (1) examine the impacts of coffee production on vegetation composition and forest productivity, (2) document farmers’ forest management practices and tree species preference, and (3) understand the challenges in conserving Zege Peninsula forests. Vegetation data were collected in 67 circular sample plots, each with 10 m radius. Household survey and focus group discussion was used to gather socioeconomic data. The results indicated that forest management practices that favor coffee production influenced the diversity and evenness of woody species. The non-coffee forest displayed significantly (p = 0.001) higher woody species diversity than coffee-based forest. The Shannon diversity and evenness were 3.23 and 0.79 in non-coffee and 2.00 and 0.52 in the coffee-based forest, respectively. However, the basal area in the coffee-based forest (23.09 m2 ha−1) showed significantly (P = 0.001) higher when compared to non-coffee (13.92 m2 ha−1). The majority (81.4%) of respondents put Ehretia cymosa, Albizia schimperiana and Millettia ferruginea as their first choice in coffee production. Timber and fuelwood extraction for the market is the main factor currently threatening Zege forest. Coffee yield reduction, mentioned by 84.5% of the respondents, owing to seasonal rainfall variability aggravated timber and fuelwood extraction for the market.